FEATURES OF THE STRUCTURE OF LATGALIAN ANIMAL ANECDOTES IN THE CONTEXT OF ANIMAL EPICS - Belasova, Inga (Via Latgalica, 2008)
The objective of the paper is to reveal the main structural features of Latgalian animal anecdotes in the context of animal epics. According to the fundamental and universal laws of folklore it can hypothetically be assumed that Latgalian animal anecdotes are an ethnic version of international zoomorphic anecdotes. When analyzing the structure of the zoomorphic anecdotes, it is essential to consider them in the context of the whole animal epic, which allows to acknowledge typological similarities and coherence in the creation of the animal images and the most typical motives. A comparative analysis illustrates that the structural features of both Latgalian and Latvian zoomorphic anecdotes are vitally associated with the whole context of animal epics, and especially with fairy tales. Some of the functions of fairy tales, as outlined by the Russian scientist V. Propp, band together, thereby forming the most typical motives of zoomorphic anecdotes, which can be found in the folklore and the literary traditions of different nations. Therefore it is possible to conclude that the Latgalian animal anecdotes preserve all those structural features of the zoomorphic anecdotes which are common for animal anecdotes in general, irrespective of the area where an anecdote is told, the nationality of a narrator or the topic. A structural analysis of the anecdotes shows the manifestation of regularities of the genre of anecdotes and its structural features, as well as a mutual interaction of the peculiarities of composition in the context of animal epics in general. A fundamental analysis of the structure of an anecdote implies identifying a motive, whose successful scientific interpretation reveals the interconnection of the structure of the fairy tales and the anecdotes. The understanding of a motive is based on the dichotomic comprehension as practiced in folklore studies, whose founder – the American folklorist A. Dandes – based it on the theory of fairy tales functions as elaborated by the Russian folklorist V. Propp. According to A. Dandes’ theory, the understanding of a motive in narrative folklore virtually merges with the understanding of the function in the morphology of fairy tales, which allows the comparison of any motive in an anecdote with the corresponding function in a fairy tale. V. Propp distinguishes 31 functions in fairy tales: eight of them have to do with the introduction (set off, prohibition, violation of the prohibition, deception, revelation of a secret, telling a secret, help, sabotage), three have to do with the nodus (mediation, initiation of counteraction, sending away or reproach), eleven have to do with the main part of the message (the first function of the sender, the hero’s response, acquisition of a magical asset, a movement of the hero, a fight, a distinctive action of a hero, victory, prevention of a shortfall, return, chase, rescue), and finally, the last nine functions (the return fails to be recognized, grudge of a false hero, a difficult task, its solution, exposure, transfiguration, punishment, wedding, reign) (Пропп 1998). Naturally, due to their compact structure, anecdotes cannot include all the functions mentioned by V. Propp. However, when banding together, several of the most typical motives of the Latgalian zoomorphic anecdotes become dominant (for example, motives of competition, truth, seeming departure, etc.), which can be found also in fairy tales about animals and other genres of animal epics. In these, every motive can be identified not on its own, but in inseparable connection with a particular message, because one motive can have different roles within different ideas. Besides, several types of artistic ideas can be distinguished in animal anecdotes as models of various life situations. Laconism in an anecdote often depends on the inclusion of a narrated element in it. Therefore, dialogues, monologues and narrated texts carry a very important meaning in an anecdote. These brilliantly reveal the most characteristic peculiarities of the genre – a short, concentrated dialogue, monologue or message elaborated to the minimum reveals personal characteristics and social realias attributed to the animals, which in reality characterize people and their mutual relations. Whereas a fairy tale’s plot contains more elaborated elements, anecdotes consist of separate compositional elements (only dialogue or monologue, or any expressive figure of repetition, etc.). Also, whereas in fairy tales the number of the plot elements is mainly constant, in the Latgalian animal anecdotes they can be variable and incomplete. As far as the compositional peculiarities of anecdotes are concerned, we can also talk about elements of verbal and nonverbal communication, which in particular cases can become a prerequisite for the creation of a comic pathos. A particular part assigns the following structure to the compositional models of the Latgalian and Latvian animal anecdotes: - components of fairy tale motives, i.e. images, compositional stages, as well as types of texts and models included into the motives, - models of structures of the anecdotes – combinations of message elements and positions of verbal and nonverbal communication. Taking into consideration that the Latgalian animal anecdotes in terms of an understanding of the motives and the organization of the structural elements show little or no difference from the Latvian anecdotes – their structure is virtually identical to the Latvian zoomorphic anecdotes – it is safe to consider the Latgalian animal anecdotes as an ethnic version of international zoomorphic anecdotes.